Final report on APMP.QM-K18.2016 key comparison on pH measurement of carbonate buffer - Asakai, Toshiaki; Maksimov, Igor; Onuma, Sachiko; Bastkowski, Frank; Sander, Beatrice; Aparicio, José Luis Ortiz; Manzano, Judith Velina Lara; Lo, Samuel M F; Poon, Desmond K F; Delgado, Mabel; Avendaño, Paola; Amaya, Ronald Cristancho; et al. (IOP Publishing, 2020)
Main text This key comparison is being performed to evaluate the degree of equivalence of measurement procedures to support the participants' claims of Calibration and Measurement Capabilities (CMCs) and to evaluate the capabilities of participants for the determination of the pH of carbonate buffer solutions. This is the fourth APMP key comparison on pH measurement following APMP.QM-K9/P16 (phosphate), APMP.QM-K19/P25 (borate) and APMP.QM-K91/P29 (phthalate). The results have the linkage to CCQM-K18.2016 (carbonate buffer) and were evaluated by comparing the results of the Physikalisch-Technische Bundesanstalt (PTB) and the National Metrology Institute of Japan (NMIJ) performing Harned cell method. The results of PTB and NMIJ were used for the definition of the Key Comparison Reference Value (KCRV). The ensuing pH value was calculated based on the Bates-Guggenheim convention to compare the results of primary and secondary methods. In this comparison measurements of pH were performed only at the temperature of 25 °C. The results demonstrated by most participants are in better agreement than those in CCQM-K18.2016. To reach the main text of this paper, click on Final Report . Note that this text is that which appears in Appendix B of the BIPM key comparison database kcdb.bipm.org/ . The final report has been peer-reviewed and approved for publication by the CCQM, according to the provisions of the CIPM Mutual Recognition Arrangement (CIPM MRA).